Identification of ATIC as a Novel Target for Chemoradiosensitization - Liu, Xiangfei; Paila, Uma Devi; Teraoka, Sharon N.; Wright, Jocyndra A.; Huang, Xin; Quinlan, Aaron R.; Gatti, Richard A.; Concannon, Patrick (International journal of radiation oncology, biology, physics, 2018)
Mutations in the gene encoding 5-aminoimidazole-4-carboxamide ribonucleotide formyltransferase/IMP cyclohydrolase (ATIC), a bifunctional enzyme that catalyzes the final 2 steps of the purine de novo biosynthetic pathway, were identified in a subject referred for radiation sensitivity testing. Functional studies were performed to determine whether ATIC inhibition was radiosensitizing and, if so, to elucidate the mechanism of this effect and determine whether small molecule inhibitors of ATIC could act as effective radiosensitizing agents. Both small interfering RNA knockdown and small molecule inhibitors were used to inactivate ATIC in cell culture. Clonogenic survival assays, the neutral comet assay, and γH2AX staining were used to assess the effects of ATIC inhibition or depletion on cellular DNA damage responses. Depletion of ATIC or inhibition of its transformylase activity significantly reduced the surviving fraction of cells in clonogenic survival assays in multiple cancer cell lines. In the absence of ionizing radiation exposure, ATIC knockdown or chemical inhibition activated cell cycle checkpoints, shifting cells to the more radiosensitive G2/M phase of the cell cycle, and depleted cellular adenosine triphosphate but did not result in detectable DNA damage. Cells in which ATIC was knocked down or inhibited and then treated with ionizing radiation displayed increased numbers of DNA double-strand breaks and a delay in the repair of those breaks relative to irradiated, but otherwise untreated, controls. Supplementation of culture media with exogenous adenosine triphosphate ameliorated the DNA repair phenotypes. These findings implicate ATIC as an effective, and previously unrecognized, target for chemoradiosensitization and, more broadly, suggest that purine levels in cells might have an underappreciated role in modulating the efficiency of DNA damage responses that could be exploited in radiosensitizing strategies.